Perancangan Sistem Informasi Pengamatan Hasil Internal Audit Berbasis Web pada PT. ABC - Hendra Bagus Setiawanto; Imam Muttaqin; M. Ichtiar Romadhoni; Nanda Alfiando Meilana; Aries Saifudin (Journal of Research and Publication Innovation, 2023)
PT. ABC is one of the food industries. One of the problems that occurs in the internal audit process is monitoring audit results that are less effective and efficient, because the internal audit that occurs today is still manual, namely the results of reports and audit monitoring still using forms that are processed using Microsoft Excel and then send the audit results via email. Along with the increasing development of information technology, currently companies need effective and efficient internal audit monitoring With these problems, a Web-based Internal Audit Monitoring Information System will be designed. The research methods used are observation methods, interviews, literature studies, system analysis and system design. This information system was created using the PHP programming language, Laravel Framework, MySQL DBMS, waterfall methods. One of the benefits and advantages of using this internal audit monitoring application is that it can monitor internal audit results more effectively, efficiently and accurately.